Black Muslimness Mobilized - Youssef J. Carter (International Institute of Islamic Thought, 2019)
West African and American-born Muslims in the Mustafawi Tariqa have been impacted by a Senegalese Islamic pedagogical tradition, which places emphasis on the role of the body as a medium for religious and spiritual training. My research examines the tremendous labor required to produce Muslimness as an embodied reality and critical resource initially in two key sites of pilgrimage—Moncks Corner, South Carolina and Thiès, Senegal—by demonstrating the important role these sister cities play in a transatlantic Sufi network. I suggest that there exists a continuity seen in the interactions of West African Muslims and African-American Muslims—a solidarity emboldened through the sufi practices out of which a broader politics of “Black Muslimness” endure. African-American and Senegalese members of the Mustafawi Tariqa identify within a broader category of ‘Black Muslim’ in the mobilization of bodies oriented toward these two sites of pilgrimage. As my extensive research reveals, Moncks Corner is the central site in which access to the Sufi order’s most charismatic living shaykh, Shaykh Arona Faye, has worked for the past two decades teaching and mentoring his students on their spiritual journeys. On the other hand, Thiès is the location where the order’s founder is buried and travelers visit the town in order to pay homage to his memory. The processes of diasporic identification seen in both sites, I argue, are grounded in both physical mobility and the particular spiritual pedagogy of the Mustafawi. In order to further elaborate how local and international solidarities are framed from within the concept of diaspora, I unpack the manner in which religious genealogies, discourses of ancestry, and the transmission of esoteric knowledge reinforce such affinities. O Allah, send blessings upon our master Muhammad, the one who precedes all others, the one whose brilliant lights radiate and fill the heavens. May Allah bless him and his family and companions in the amount of every grain of sand and every star in the sky. (al-ṣalāt al-samawiyya).